Expression and function of gastrin‐releasing peptide (GRP) in normal and cancerous urological tissues. (March 2014) - Ischia, Joseph; Patel, Oneel; Bolton, Damien; Shulkes, Arthur; Baldwin, Graham S.
Abstract : Gastrin‐releasing peptide (GRP) acts as an important regulatory peptide in several normal physiological processes and as a growth factor in certain cancers. In this review we provide a comprehensive overview of the current state of knowledge of GRP in urological tissues under both normal and cancerous conditions. GRP and its receptor, GRP‐R, are expressed in the normal kidney and renal cancers. GRP can stimulate the growth of renal cancer cells. GRP and GRP‐R are expressed in prostate cancer and GRP can stimulate the growth of prostate cancer cell lines. Importantly, GRP is a key neuroendocrine peptide, which may be involved in the progression of advanced prostate cancer and in the neuroendocrine differentiation of prostate cancer. Recent animal studies have shown that GRP and GRP‐R are an integral part of male sexual function and play a crucial role in spinal control of erections and ejaculation.